Menggali Kreativitas, Kepercayaan Diri Dan Pelatihan Kewirausahaan: Penentu Niat Berwirausaha Di Kalangan Mahasiswa - Ida Ketut Kusumawijaya; Partiwi Dwi Astuti; I Nyoman Sunarta (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2021)
ABSTRACT: This study aims to analyze the determinants of entrepreneurial intention by examining the effects of creativity, self-confidence, entrepreneurial training, subjective norms, entrepreneurial attitude and perceived control. This research was conducted on student majoring in business at private university in Bali with a population of 7,246 people. The sample is 379 and data is collected using a questionnaire that returns 279 with a response rate of 62.56%. Testing the research model using PLS-SEM with WarpPLS 7.0. The results show that creativity, self-confidence can significantly affect entrepreneurial attitude; entrepreneurial training can significantly affect perceived control; subjective norms, entrepreneurial attitude and perceived control can significantly influence entrepreneurial intention. This study finds the role of creativity, self-confidence and entrepreneurial training as determinants of entrepreneurial intention among business students in Bali.